Experiential Learning: Experience as the Source of Learning and Development - Kolb, David A. (Pearson Education, 2014)
Experiential learning is a powerful and proven approach to teaching and learning that is based on one incontrovertible reality: people learn best through experience. Now, in this extensively updated book, David A. Kolb offers a systematic and up-to-date statement of the theory of experiential learning and its modern applications to education, work, and adult development.
Keywords: formation des adultes